Rotavirus infections in domestic animals - CHATZOPOULOS (Δ.Χ. ΧΑΤΖΟΠΟΥΛΟΣ), D. C.; ATHANASIOU (Λ.Β. ΑΘΑΝΑΣΙΟΥ), L. V.; SPYROU (Β. ΣΠΥΡΟΥ), V.; FTHENAKIS (Γ.Χ. ΦΘΕΝΑΚΗΣ), G. C.; BILLINIS (Χ. ΜΠΙΛΛΙΝΗΣ), C. (Journal of the Hellenic Veterinary Medical Society, 2017)
Rotaviruses are major enteric pathogens of humans and a wide variety of animals. Rotavirus infections have a worldwide prevalence. The viral genome is composed of 11 double-stranded RNA segments with six structural and five or six non-structural proteins. Over 35,000 strains have been identified and classified into five main (A, B, C, D, E) and three additional tentative (F, G, H) serotype groups. A binary classification system has been proposed defining ‘G’ or ‘P’ types, with at least 27 G and 35 P genotypes reported thusfar. The virus is transmitted primarily by the faecal-oral and oral routes. After attachment, entry into the host cells occurs through direct entry, fusion or endocytosis. Main mechanisms of Rotavirus-induced diarrhoea involve extensive enterocyte losses and nutrient disdigestion and malabsorption. Clinical features of Rotavirus infections range from asymptomatic infections to fulminant disease leading to rapid death. In calves, lambs and kids, piglets and foals, salient sign of the disease is diarrhoea; diarrhoeic faeces are white, yellow or, in severe cases, blood-tinted or frank haemorrhagic. In dogs and cats, the infection occurs usually as self-limiting diarrhoea. Avian Rotavirus infections are characterized by enteritis, growth depression and/or growth retardation. Definitive diagnosis of the infection can only be achieved by laboratory tests, including electron microscopic examination, immunohistochemical examination, immunofluorescence, ELISA, latex agglutination and molecular techniques. There is no specific treatment against Rotavirus infections. Treatment is based in providing supportive care and managing clinical signs and potential complications. Effective vaccines, containing inactivated, recombinant or attenuated strains of the virus, are available. Challenge studies have shown the ease of the virus in cross-infecting various animal species; animal strains of the virus may cross species and infect humans. Due to the ability of the virus to overcome species barriers, animal strains may act as natural source of viral genomes, promoting mutations and creating new viral genotypes, whose virulence cannot be predictable.